2017
DOI: 10.1590/0001-3765201720160067
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Psidium guajava leaves: phenolic compounds and inhibitory potential on digestive enzymes

Abstract: Leaves of Psidium guajava L. (guava) have been widely used in the popular way for prevention and treatment of various diseases. Thus, the objective of this study was to evaluate the inhibitory potential of leaves aqueous extract from three cultivars of P. guajava (Pedro Sato, Paluma and Século XXI) on α-amylase, α-glycosidase, lipase, and trypsin enzymes, in the presence or not of simulated gastric fluid and to determine the content of phenolic compounds by high performance liquid chromatography. All cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
2
31
1
1
Order By: Relevance
“…This strong anti‐lipase activity may be due to the high level of quercetin in our leaves’ extract. Similar enzymatic results were found by Simao, Marques, Marcussi, and Correa () in an aqueous extract of leaves of Psidium guajava (Myrtaceae). Those authors reported that the potential use of this plant as an adjuvant in the treatment of dyslipidemias and obesity, following its richness in catechin and quercetin.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This strong anti‐lipase activity may be due to the high level of quercetin in our leaves’ extract. Similar enzymatic results were found by Simao, Marques, Marcussi, and Correa () in an aqueous extract of leaves of Psidium guajava (Myrtaceae). Those authors reported that the potential use of this plant as an adjuvant in the treatment of dyslipidemias and obesity, following its richness in catechin and quercetin.…”
Section: Resultssupporting
confidence: 87%
“…This strong anti-lipase activity may be due to the high level of quercetin in our leaves' extract. Similar enzymatic results were found by Simao, Marques, Marcussi, and Correa (2017) in an aqueous extract of leaves of Psidium guajava (Myrtaceae). Those…”
Section: Methods Asupporting
confidence: 84%
“…The study revealed that all cultivars showed the same phenolic composition but in different proportions, where catechin was the major compound in Paluma cultivar, epigallocatechin gallate, and revesterol in Pedro Sato and syringic acid, o-coumaric acid, and quercetin for Século XXI [43]. The enzyme inhibition occured in major proportion for Século XXI cultivar against alpha-amylase before the exposure to gastric fluid (14410.60 ± 38 inhibited enzyme unit in µmol·min −1 ·g −1 ) and Paluma against alpha-glucosidase before (28.82 ± 0.02 inhibited enzyme unit in µmol·min −1 ·g −1 ) and after exposure (2.59 ± 0.06 inhibited enzyme unit in µmol·min −1 ·g −1 ) [43]. Pedro Sato revealed the highest inhibitory effect against lipase before (36.45 ± 0.68 inhibited enzyme unit in µmol·min −1 ·g −1 ) and after exposure (43.33 ± 1.80 inhibited enzyme unit in µmol·min −1 ·g −1 ) [43].…”
Section: Polyphenolic Compounds-fruits Vegetables and Plantsmentioning
confidence: 98%
“…Simão and colleagues tested the inhibitory potential of an aqueous extract from the leaves of three cultivars of Psidium guajava (guava) on α-amylase, α-glucosidase, lipase and trypsin enzymes. These studies were done in the presence or absence of simulated gastric fluid and the content of phenolic compounds was determined [43]. The study revealed that all cultivars showed the same phenolic composition but in different proportions, where catechin was the major compound in Paluma cultivar, epigallocatechin gallate, and revesterol in Pedro Sato and syringic acid, o-coumaric acid, and quercetin for Século XXI [43].…”
Section: Polyphenolic Compounds-fruits Vegetables and Plantsmentioning
confidence: 99%
See 1 more Smart Citation